Beyond political Islam: exploring discourses and uses of three popular global Islamic social media initiatives - Basiony, Dina Mohamed (AUC Knowledge Fountain, 2013)
This study explores the discourses employed in three growingly popular global Islamic social media pages (GISMP), and examines their potential impact on identities of young Muslim followers across the globe. The initiatives are; Celebrate Mercy, Productive Muslim and Quran Weekly. The three sites are among today’s most popular Islam-based social media pages. The analysis highlights each site’s discourses about the Muslim identity, relevance of Qur’an to youth, and representation of central figure, Prophet Muhammad- as well as how the pages address issues like terrorism, violence and the religious other. The aim is to examine how major Islamic tenets are being propagated to masses of Muslim youth around the world today via social media, how this influences our understanding of the uses of social media, and how this potentially influences followers of the world’s second largest religious population. A survey of site users was conducted to examine the uses/reactions of followers towards the initiatives’ work. The survey yielded 900 responses from Muslim youth in eight different regions across the globe. Additionally, in-depth interviews were conducted with the pages’ founders to provide insight into their motivations and how they see their work influencing both page followers and the global Muslim community. Survey results illustrated that mainstream Muslim youth find leaders of Muslim majority countries unrepresentative of Islam, and feel under-represented in traditional media. They use social media outlets to reclaim their own narrative, express and boost their Muslim identity, and connect with members of the global Muslim community, the ummah. The study shows how certain GISMP have the potential to indirectly counter anti-Islam discourses in mainstream traditional/social media outlets. The study also points to the potential influence of popular GISMP in connecting and mobilizing young Muslims around the world.